Neurological Outcome of Transpedicular Screw Fixation for Spontaneous Spondylolisthesis - Abdul Bari, Shafaat Hussain, Muhammad Asad Iqbal, Sahibzada Aneesullah, Saeed Taj Din (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Spontaneous spondylolisthesis is a degenerative spinal condition that may result in mechanical instability, neurological deficits, and often surgical intervention. Transpedicular screw fixation is frequently performed to achieve spinal stabilization and decompress the involved nerve roots. However, there is little local data concerning its effects on neurological recovery. Examine the neurological and functional outcomes of transpedicular screw fixation in patients with spontaneous spondylolisthesis. Methods: This prospective study included 57 patients with radiologically confirmed spontaneous spondylolisthesis who underwent transpedicular screw fixation between January 2021 and January 2022 at the Department of Orthopaedics and the department of Neurosurgery, PAEC General Hospital, Islamabad. Pre- and postoperative assessments included neurological examination, Visual Analog Scale (VAS) for pain, Oswestry Disability Index (ODI), and Modified McNab criteria. Data were analyzed to evaluate changes in motor and sensory function, pain levels, and functional ability. Results: Out of 57 patients, 42 (73.7%) showed neurological improvement postoperatively, while 12 had no change, and 3 experienced worsening symptoms. Motor and sensory functions improved significantly (p = 0.002 and p = 0.014, respectively). Mean VAS scores dropped from 7.8 preoperatively to 2.6 postoperatively (p < 0.001), and functional outcomes measured by ODI and McNab criteria also demonstrated statistically significant improvement. Complications were minimal and did not affect long-term recovery. Conclusion: Transpedicular screw fixation is an effective and safe surgical option for managing spontaneous spondylolisthesis, offering substantial neurological recovery, pain relief, and functional improvement. Early surgical intervention and meticulous technique are key to achieving favorable outcomes. Keywords: Spondylolisthesis, Transpedicular screw fixation, Neurological outcome, Lumbar spine, Spinal fusion, Functional recovery, Back pain surgery